Renal neoplasms - Onur, Mehmet Ruhi; Bhatt, Shweta; Dogra, Vikram S.; MacLennan, Gregory T. (Springer-Verlag London Ltd, 2013)
The incidence of kidney cancer has been increasing steadily for the past 65 years. Kidney cancer incidence and mortality rates are more than twice as high in men as in women. Renal cell carcinoma (RCC) accounts for 3 % of adult malignancies. Although RCC comprises the majority of solid renal neoplasms, benign tumors constitute a significant proportion of surgically resected renal masses. Ultrasound is the first method in evaluation of patients with suspected renal mass. Computed tomography (CT) is useful in detecting and characterizing renal masses and in staging renal malignancies (Table 1.1). Magnetic resonance imaging (MRI) can reveal internal structure of the lesions. © Springer-Verlag London 2013.